Investigation of an antitumor drug-delivery system based on anti-HER2 antibody-conjugated BSA nanoparticles. Issue 4 (April 2018) - Zhang, Nan; Zhang, Jiangnan; Wang, Pei; Liu, Xinyang; Huo, Pengchao; Xu, Yue; Chen, Wenjie; Xu, Hongying; Tian, Qingfeng
Abstract : Conjugation of a monoclonal antibody with a nanoparticle often improves its specificity and drug loading in cancer therapy. In this study, we prepared a novel targeting nanodrug-delivery system using 2-methoxy-estradiol (2-ME) based on anti-human epidermal growth factor receptor 2 (HER2) antibody-modified BSA to improve the clinical application and antitumor effect of 2-ME. 2-ME-loaded albumin nanoparticles (2-ME-BSANPs) were prepared using a desolvation method and the anti-HER2 antibodies were conjugated to 2-ME-BSANPs (HER2-2-ME-BSANPs) using the coupling agent, succinimidyl 3-(2-pyridyldithio)propionate. HER2-2-ME-BSANPs were characterized using SDS-polyacrylamide gel electrophoresis, an agglutination test, and an immunofluorescence assay. We found that mouse anti-human anti-HER2 monoclonal antibody was successfully conjugated to the 2-ME-BSANPs. Thereafter, the in-vitro and in-vivo toxicities were evaluated using two cancer cell lines, SK-BR-3 (HER2-overexpressing) and MCF-7 (HER2-underexpressing), using classic pharmacological methods and in-vivo imaging technology. We found that the HER2-2-ME-BSANPs retained the immunospecificity of the anti-HER2 monoclonal antibody, rapidly localized to HER2 receptors, and could be used for targeted cancer therapy.